Business Irregularities of Oyster Chicken Meatball Stalls in Bantul, Yogyakarta - Sabda Dian Nurani Siahaan; Azalia Kartika Rudyani; Insania Asyifa Hasibuan; Melda Siburian; Devi Intan Sitompul; Riandi Paskah Wijaya Sagala (Jurnal Ekonomi dan Bisnis Digital, 2023)
It harms the seller or buyer either financially or in other areas. Deviant business activities in this study relate to business practices that do not comply with these rules. The method used in this research is a qualitative or quasi-experimental method. The author uses this method because there is limited time to directly review this matter appropriately and effectively. In this study, we, the authors, invite readers to know and understand how MSMEs in Indonesia, especially meatball stalls in the city of Bantul, Yogyakarta, carry out fraudulent business actions, causing losses to the health of the people who consume them.